El desarrollo afectivo de los padres en el proceso de enseñanza aprendizaje de los niños de dos a tres años de la modalidad Creciendo con nuestros hijos, María Auxiliadora y El Tránsito del Ministerio de Inclusión Económica y Social - Quito Sur. - Torres Herrera, Beatriz Aurora (2020)
This research work was born from the problem of children from 2 to 3 years old who attend the service in the modality Growing with our children - Misión Ternura. At the time of attending the group activity, inadequate procedures were noted in their behavior, it is here, where this research proposal arose, with the aim of determining the incidence of affective development in the teaching-learning processes that parents transmit to their children through the good treatment in the socio-affective aspect of children from 2 to 3 years old at the CNH-MT María Auxiliadora and El Tránsito. These workshops, aimed at educators, family members and parents, who are the first contact with the infant, are the ones that influence the procedure, either by the environment where they live or by habits. The methodology used in this research was of a quantitative and qualitative approach, obtaining the data in a structural way, thus giving, as a result, the low level of stimulation. Few forms of development in teaching are derived from surveys directed at parents and under the observation of educators, also counting on the opinion of the authorities of the Quito South District of MIES, leaving a viable proposal with the teachings for families and children. educators of the service, emphasizing these results obtained and hoping to arrive with the workshops "EL CLUB DE ALEGRIA" aimed at creating in them the importance of the growth and care of the child.